Improving the Quality of Survey Data on College Campus Woman Abuse: The Contribution of a Supplementary Open-Ended Question - DeKeseredy, Walter S. (Violence against women, 2021)
Obtaining accurate survey data on the prevalence of woman abuse in institutions of higher education continues to be a major methodological challenge. Underreporting is difficult to overcome; yet, there may be effective ways of minimizing this problem. One is adding a supplementary open-ended question to a primarily quantitative questionnaire. Using data derived from the Campus Quality of Life Survey (CQLS), this article examines whether asking respondents to complete such a question increases the prevalence rates of four types of woman abuse and provides information on behaviors that are not included in widely used and validated measures of these harms.